FUNGSI SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PELAPORAN KEUANGAN PADA PDAM TIRTANADI PROVINSI SUMATERA UTARA - WESLY SIMANJUNTAK (LP2MTBM MAKARIOZ, 2019)
The company is expected to be able to implement an information system that can be used by the company. Management requires an accounting information system that can help in gathering data about company activities, and changing that data to become accurate information. The information system provides accounting and financial information along with other information obtained from routine accounting transaction processes. Information systems are important for the company. Information is collected according to user needs. This study aims to find out how accounting information systems are used to improve the efficiency and effectiveness of financial reporting. The research method used is descriptive-comparative analasis. Based on research conducted at the company, the accounting information system of PDAM Tirtanadi, North Sumatra Province, Medan has been running well. The data input process starts from direct payment to the counter, new installation transaction, this can be seen from the start of the customer registering for a new tide transaction, the customer is quite satisfied with the information given in that section from the start filling out the form then describes the house plan occupied for make it easier for officers to install the new clean water connection. Input data, processes, and outputs are carried out systematically which is assisted by a computerized system, helping computerized activities improve the efficiency and effectiveness of financial reporting